2006
DOI: 10.1021/ja058509n
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of G-Quadruplex DNA and Inhibition of Telomerase Activity by Square-Planar Nickel(II) Complexes

Abstract: Two new alkylamine-substituted nickel(II)-salphen complexes have been prepared and their interactions with DNA investigated. FRET studies have shown that these complexes have a remarkable ability to stabilize G-quadruplex DNA. Furthermore, TRAP/Taq assays have shown that these complexes inhibit telomerase at low micromolar concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
237
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(244 citation statements)
references
References 20 publications
6
237
0
1
Order By: Relevance
“…A number of small molecules have been identified to selectively bind and stabilize the telomeric G-quadruplex DNA in vitro. 4 Phenanthroline derivatives attracted our attention not only because of their pharmacological effects in many drugs, but also because of their functional role in DNA ligands. Recently, Neidle and co-workers reported that a platinum-phenanthroline square complex can induce a high degree of quadruplex DNA stabilization and inhibit telomerase activity.…”
mentioning
confidence: 99%
“…A number of small molecules have been identified to selectively bind and stabilize the telomeric G-quadruplex DNA in vitro. 4 Phenanthroline derivatives attracted our attention not only because of their pharmacological effects in many drugs, but also because of their functional role in DNA ligands. Recently, Neidle and co-workers reported that a platinum-phenanthroline square complex can induce a high degree of quadruplex DNA stabilization and inhibit telomerase activity.…”
mentioning
confidence: 99%
“…The sequestering of the telomere in a G-quadruplex structure inhibits the catalytic lengthening activity of telomerase, which requires the 3 0 end to be in a non-folded form (Zahler et al, 1991). G-quadruplex structures are readily bound and stabilised by small molecule ligands such as RHPS4 (3,11-difluoro-6,8,13-trimethyl-8H-quino[4,3,2-kl]acridinium methosulfate, a pentacyclic salt, NSC 714187, Figure 1A) (Gowan et al, 2001) and other G-quadruplex ligands Reed et al, 2006;Tahara et al, 2006). A characteristic of RHPS4 is a low overall growth-inhibitory activity in short-term cytotoxicity assays such as the 48 h sulforhodamine B assay used by the NCI 60 cell line screen (mean IC 50 13.18 mM), but potent inhibition of telomerase enzyme activity (IC 50 0.33 mM) (Heald et al, 2002).…”
mentioning
confidence: 99%
“…The inhibition can be obtained through the stabilization of the quadruplex structures performed by small molecules whose features are: (1) a π-delocalized system that is capable to stack on the face of a guanine quartet; (2) a partial positive charge that is able to stay in the center of the quartet, increasing stabilization through the substitution of the cationic charge of the potassium or sodium that normally occupies that site; (3) the presence of positively charged substituents capable to interact with the grooves and loops of the quadruplex and with the negatively charged backbone phosphates. Over ten years ago, the first example of a G quadruplex binder based on metal salophens was reported, 27 ( Figure 18) [40]. The planar nickel(II) complexes 27a and 27b are excellent G-quadruplex DNA stabilizers.…”
Section: Introductionmentioning
confidence: 99%